Having the right neighbors: how tree species diversity modulates drought impacts on forests - Grossiord, Charlotte (The New phytologist, 2020)
Summary Droughts are a rising concern for terrestrial ecosystems, particularly for forests where drought‐induced reductions in tree growth and survival are reported. Biodiversity has long been acknowledged as an important component modulating ecosystem functions, including mitigating their vulnerability to climate‐related stresses. Yet the impact of tree diversity on forest vulnerability to drought is unclear. In this review, consistent mechanisms are identified by which tree diversity could reduce vulnerability to drought and emerging evidence is revealed that tree diversity is not systematically positively related to drought resistance in forests. A path is suggested to further increase our knowledge on this subject in the face of climate change, proposing standardization of methods to quantitatively establish diversity impacts on the drought resistance of forests. Charlotte Grossiord is an honourably mentioned finalist of the 2018 New Phytologist Tansley Medal competition for excellence in plant science. See Lennon & Dolan, in this issue of New Phytologist (2020, 228: 5) for more details.